Pengaruh Pelaksanaan Pemberian Makanan Tambahan Penyuluhan (PMT-P) Terhadap Pola Makan Dan Status Gizi Pada Balita (12-59 Bulan) Di Bakaran Batu - Sartika Simanjuntak; Haripin Togap Sinaga (Journal of Pharmaceutical and Sciences, 2023)
Indonesia is a developing country that has complex problems, especially regarding nutrition. Based on SSGI results (2021), Deli Serdang Regency has (underweight) 11.30% and 9.5% (wasted). The consequences of malnutrition have an impact on the growth and development of children under five, causing malnutrition and stunting. Therefore, the government's efforts to overcome nutritional problems by issuing Law No. 36 of 2009 concerning Health articles 170 and 171. Prevention efforts are carried out through growth monitoring at posyandu while toddlers who have nutritional problems are followed up with a supplementary feeding program (PMT). This study aims to assess the effect of PMT Extension on eating patterns and nutritional status before giving additional food as reference material for information regarding PMT Extension which is popular with toddlers at the Community Health Center and Village in Bakaran Batu. The method used in this research is primary data collected directly by researchers and secondary data to complete research needs obtained from Posyandu in Bakaran Batu Dusun 4 and 5. This type of research is Quasi Experimental with a one group pre and post test design. The population in the study were all toddlers who attended Posyandu Wijaya Kesuma Dusun 4 and 5 with a sample of 30 people